2009
DOI: 10.1039/b914068a
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of difluorinated carbasugar phosphates from trifluoroethanol

Abstract: Difluorinated cyclohexene diols (prepared from trifluoroethanol) can be elaborated to racemic analogues of phosphorylated sugars via regioselective protection and phosphorylation of the exposed C-1 hydroxyl group. Cis-diol protection was achieved using stannylene methodology, though the regioselectivity depended on the orientation of the methyl group at C-5. UpJohn dihydroxylation is effective with the phosphotriester in place and global deprotection to the tetrol monophosphates is efficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Approximately at the same time as the studies using 2,2-difluoropent-4-enoic acid described in section were carried out, Percy and co-workers performed a thorough investigation concerning the synthesis of gem -difluoro eight-membered cyclooctenones and carbohydrate analogues using trifluoroethanol 68 as the common starting material. Actually, these reports belong to a more general study on the use of trifluoroethanol as starting material for the preparation of fluorinated building blocks in the synthesis of complex molecules containing the gem -difluoro moiety . In this context, the authors used their own previously reported methodologies , to achieve fluorinated 1,9-diene precursors of eight-membered carbocycles by RCM (Scheme ) .…”
Section: Ring-closing Metathesis (Rcm) With Fluorinated Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately at the same time as the studies using 2,2-difluoropent-4-enoic acid described in section were carried out, Percy and co-workers performed a thorough investigation concerning the synthesis of gem -difluoro eight-membered cyclooctenones and carbohydrate analogues using trifluoroethanol 68 as the common starting material. Actually, these reports belong to a more general study on the use of trifluoroethanol as starting material for the preparation of fluorinated building blocks in the synthesis of complex molecules containing the gem -difluoro moiety . In this context, the authors used their own previously reported methodologies , to achieve fluorinated 1,9-diene precursors of eight-membered carbocycles by RCM (Scheme ) .…”
Section: Ring-closing Metathesis (Rcm) With Fluorinated Derivativesmentioning
confidence: 99%
“…In addition to the aforementioned decade-long thorough study of fluorinated cyclooctenone derivatives, Percy’s group also investigated the synthesis of difluorinated carbasugar derivatives . Substitution of the endocyclic oxygen atom of a saccharide by a CH 2 results in major changes in its conformation and, more importantly, in its reactivity .…”
Section: Ring-closing Metathesis (Rcm) With Fluorinated Derivativesmentioning
confidence: 99%
“…Compound 114 was dihydroxylated to give racemic 6-deoxygem-difluorocarbasugar 115 (Scheme 30). 49 3.2.3 CYCLOADDITIONS. A gem-difluorinated carbacyclic scaffold, resembling a carbasugar, was synthesized by Singh using an intramolecular [3 + 2] cycloaddition.…”
Section: Carbacyclisation Of Fluorinated Backbonementioning
confidence: 99%
“…When the atoms at one of the termini are fluorines, additional stericr epulsion will arise, raising the reaction barrier. However,a ns p 2 carbon bearing two fluorine atoms is rehybridisingt os p 3 duringt he course of the reaction, which will help to lower the barrier; the effect is well-known in rearrangement chemistry,h aving been observed in Claisen [25] and oxy-Cope [26] rearrangements inter alia. If the two effects are at or close to balance, the electrocyclisations of the fluorinated systems should not be significantly disadvantagedr elative to their desfluoroc ounterparts, and dehydrofluorinationtoaf luoroarene will provide as trong overall drivingf orce.…”
Section: Introductionmentioning
confidence: 99%